The next-to-minimal supersymmetric extension of the standard model reviewed - Maniatis, Markos (International journal of modern physics. A, Particles and fields, gravitation, cosmology, 2010)
The next-to-minimal supersymmetric extension of the Standard Model (NMSSM) is one of the most favored supersymmetric models. After an introduction to the model, the Higgs sector and the neutralino sector are discussed in detail. Theoretical, experimental, and cosmological constraints are studied. Eventually, the Higgs potential is investigated in the approach of bilinear functions. Emphasis is placed on aspects which are different from the minimal supersymmetric extension.
Gesehen am 03.05.2023